The Effect of Prices and Store Attempt on Purchase Decisions That Impact on Customer Satisfaction In Hypermarkets In Bandung - Dadang Munandar (PINISI Discretion Review, 2019)
This study aims to determine the effect of price and store atmosphere on purchasing decisions that have an impact on consumer satisfaction at Hypermarkets in Bandung. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that the price has a significant effect on purchasing decisions by 35.1%, hypothesis testing obtained a significance of 0.000 <0.05. Store atmosphere has a significant effect on purchasing decisions by 44.6%, hypothesis testing obtained a significance of 0.000 <0.05. Prices and store atmosphere simultaneously have a significant effect on purchasing decisions by 51.1%, hypothesis testing is obtained with a significance of 0.000 <0.05. Purchasing decisions have a significant effect on consumer satisfaction by 31.9%, hypothesis testing obtained a significance of 0.000 <0.05.